Quantized Event-triggered feedback control under fuzzy system with time-varying delay and Actuator fault. (February 2020) - Aslam, Muhammad Shamrooz; Qaisar, Irfan; Saleem, Muhammad Ahsan
Abstract: This paper is concerned to address the problem of quantized event-based H ∞ control for networked control systems (NCS's) under time-varying delay with actuator fault. The feedback NCS's has been demonstrated as a nonlinear system with time-varying. Event-triggered communication scheme and a quantization scheme are also co-designed to overcome the bandwidth utilization. According to this scheme, data will only transmit when it reaches the threshold value. Furthermore a T–S fuzzy delay model is employed to approximate the nonlinear dynamics of the NCS's. In addition a novel Lyapunov function is introduced to establish H ∞ performance index in the term of linear matrix inequalities (LMIs). Finally, a truck-trailer example is provided to demonstrate the advantage and effectiveness of the anticipated results.